2017
DOI: 10.1158/1078-0432.ccr-16-1095
|View full text |Cite
|
Sign up to set email alerts
|

High Estrogen Receptor β Expression Is Prognostic among Adjuvant Chemotherapy–Treated Patients—Results from a Population-Based Breast Cancer Cohort

Abstract: Purpose: Isoform-specific tumor estrogen receptor b (ERb) expression may hold prognostic information in breast cancer, especially among endocrine-treated breast cancer patients. The study's purpose was to evaluate ERb isoform 1 (ERb1) expression in relation to tumor characteristics, ESR2 genotypes, and prognosis in different treatment groups.Experimental Design: A population-based prospective cohort of 1,026 patients diagnosed with primary invasive breast cancer in Lund, Sweden, between October 2002 and June 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 52 publications
0
26
0
Order By: Relevance
“…CTCs highly expressed HAND2, which is reported to decrease ESR1 transcriptional activity. 33 CTCs also strongly expressed WNT8A, 34 PIK3CB, 35 and ESR2, 36 in addition to the OR52H1, CATSPER4, and CLRN1 genes, which were not previously associated with breast cancer. EGFR was expressed in half of the CTCs (Fig.…”
Section: Discussionmentioning
confidence: 81%
“…CTCs highly expressed HAND2, which is reported to decrease ESR1 transcriptional activity. 33 CTCs also strongly expressed WNT8A, 34 PIK3CB, 35 and ESR2, 36 in addition to the OR52H1, CATSPER4, and CLRN1 genes, which were not previously associated with breast cancer. EGFR was expressed in half of the CTCs (Fig.…”
Section: Discussionmentioning
confidence: 81%
“…Previous studies suggested that the high expression of an alternative ER isoform, ESR2 (encoding ERβ), was associated with favorable BC prognosis and that the association might depend on the ratio of ESR1 and ESR2 (ERα and ERβ) 24,25 . Consistently, we observed that patients with increasing ESR1/ESR2 ratio tended to have poorer survival (HR=1.5, 95% CI=0.7-3.3, P=0.27, adjusting for age and stage) in TCGA luminal patients.…”
Section: Discussionmentioning
confidence: 99%
“…Upregulation of ERb1 or its splice variant ERb5 enhanced the efficacy of doxorubicin and cisplatin in breast cancer cells (31,32). Consistently, high expression of ERb1 has recently been associated with better prognosis in chemotherapy-treated ERa-negative breast cancer (33,34). In addition, ligand-mediated activation of ERb has been shown to sensitize malignant pleural mesothelioma cells to cisplatin and pemetrexed therapy by suppressing AKT signaling that leads to PARP-dependent proapoptotic cell death (35).…”
Section: Introductionmentioning
confidence: 88%
“…High expression of ERb1 has been associated with better prognosis in chemotherapy-treated breast cancer patients (33). To investigate whether a similar association occurs in lung cancer, we tested the correlation between ERb1 and survival in published Kaplan-Meier plotter datasets (38) and found that chemotherapy-treated ESR2 high NSCLC patients have better clinical outcome compared with ESR2 low patients (Supplementary Fig.…”
Section: Erb1 Sensitizes P53-defective Nsclc Cells To Chemotherapeutimentioning
confidence: 96%